Differential impact of learning path based versus conventional instruction in science education. (August 2016) - De Smet, Cindy; De Wever, Bram; Schellens, Tammy; Valcke, Martin
Abstract: Learning paths have the potential to change the teaching and learning interaction between teachers and students in a computer-supported learning environment. However, empirical research about learning paths is scarce. Previous studies showed that the low adoption of learning paths can be linked to the lack of knowledge on the part of teachers about learning path design and its implementation. In the present study, which was undertaken in the context of a biology course in secondary education, 496 14- to 15-years old secondary school students in Flanders were assigned to either learning path based or conventional instruction during classroom activities. The aim was to analyze the differential impact of the instructional formats on learning outcomes, considering variations in group setting and group composition. Given the focus on science learning, gender was also considered. Multilevel analysis was applied, and the results show empirical evidence for superior performance for both boys and girls in the learning path condition as compared with that in the conventional condition. In addition, when girls collaborate, they perform best within same-sex groups, whereas boys achieve better results in mixed-gender groups. The implications of the findings are important for tackling the gender gap in science learning. The findings can lead to guidelines for teachers who want to implement learning paths within an optimal learning environment design. Highlights: This study investigates the impact of instructional methods on learning outcomes. Special attention was paid to group setting, group composition, and gender. Evidence was found for superior performance in studying via a learning path. Boys performed better in mixed-gender groups, and girls in same-sex groups.